Rock, cries and reality. An approach to the music of Los Beatniks and Los Abuelos de la Nada (Revista Argentina de Musicología, 2018)
The critical reading of the national and interactional social circumstances in which the "National Rock" movement in Argentina is inserted will be one of the most outstanding features of its first period, up to the decade of the eighties. The cry of its songs translates into a textual message of particular importance among these criticisms of the prevailing system and proposals for a new society. This message will he the specific feature of that aesthetic of' the collective cry that this generation will get from the most popular musical groups of the moment and, indirectly, from the North American Beat Generation. From this perspective, we propose a semiotic analysis of the various characteristics and methods of expression or the cry within the first recordings of Los Beatniks and Los Abuelos de la Nada.